Photoperiodic Signaling and Senescence, an Ancient Solution to a Modern Problem? - Serrano-Bueno, Gloria; Sánchez de Medina Hernández, Víctor; Valverde, Federico (Frontiers in Plant Science, 2021)
The length of the day (photoperiod) is a robust seasonal signal originated by earth orbital and translational movements, a resilient external cue to the global climate change and a predictable hint to initiate or complete different developmental programs. In eukaryotic algae, the gene expression network that controls the cellular response to photoperiod also regulates other basic physiological functions such as starch synthesis or redox homeostasis. Land plants, evolving in a novel and demanding environment, imbued these external signals within the regulatory networks controlling organogenesis and developmental programs. Unlike algae that largely have to deal with cellular physical cues, within the course of evolution land plants had to transfer this external information from the receiving organs to the target tissues, and mobile signals such as hormones were recruited and incorporated in the regulomes. Control of senescence by photoperiod, as suggested in this perspective, would be an accurate way to feed seasonal information into a newly developed function (senescence) using an ancient route (photoperiodic signaling). This way, the plant would assure that two coordinated aspects of development such as flowering and organ senescence were sequentially controlled. As in the case of senescence, there is growing evidence to support the idea that harnessing the reliability of photoperiod regulation over other, more labile signaling pathways could be used as a robust breeding tool to enhance plants against the harmful effects of climate change.